Utilization of asphalt plant waste powder as a partial cement replacement in concrete - Rafiza Abd Razak; Zuraida Zulkifli; Mohd Mustafa Al Bakri Abdullah; Zarina Yahya; Md Azree Othuman Mydin; Shafiq Ishak; Marcin Nabialek; Bartlomiej Jez (Archives of Civil Engineering)
Asphalt Plant Waste Powder (APWP) is a sort of waste that asphalt mixing facilities produce in enormous amounts. These materials have the potential to cause a plethora of new health and environmental concerns; thus, they should be changed into something more useful and environmentally friendly. This substance comprising silicon and aluminium, which can be utilised as a cement substitute or in building. Utilization of APWP is a novel, since very limited research has used this material especially in concrete. This study will evaluate the use of Asphalt Plant Waste Powder (APWP) as a cement substitute in order to produce regular, usable concrete. This study aims to determine the ideal amount of cement replacement by APWP for use as a building material and to manufacture normal concrete with a density of less than 2400 kg/m3. To partially replace cement, four proposed percentages of 10%, 20%, 30%, and 40% are utilised. Compressive and flexural strength were examined at 28 days throughout the project. All specimens were water-cured prior to being examined. The optimal replacement of cement by APWP is therefore 10% with compressive strength of 53.75 MPa, density of 2456 kg/m3, Ultra Pulse Velocity (UPV) of 3.82 km/s, and flexural strength of 5.84 MPa. Consequently, it is suggested that APWP can be utilised as a cement alternative at a replacement rate of 10%.